The State JFHQ -- Getting it Right with NORTHCOM - Dahlman, Richard H. (2008)
What is the State Joint Force Headquarters (JFHQ) role and its interaction with NORTHCOM? Each of the 50 states has its own JFHQ. The state JFHQ provides the Governor and the Adjutant General with a planning and staffing cell for contingencies. This is the first line of defense in a state emergency. What are the challenges for the state JFHQ? How does NORTHCOM effectively assist with this process after the governor has requested federal support? The well-being of the people of every state in this nation depends on these professional relationships. Establishing roles and a common understanding is essential to good operating practice for any business. The business of homeland defense and crisis management necessitates correctly establishing these relationships before a crisis occurs. USAWC Strategy Research Project.